Desarrollo cognitivo de los niños que hacen uso del internet (video juegos y redes sociales) de la Institución educativa Liceo El Saber del Municipio de Zarzal (V) (2024)
This work was developed with the purpose of knowing the cognitive effects that are the result of excessive use of the Internet in children between the ages of 8 and 10, since this is a transcendental stage in their school development, since as Leiva explains and Zuleta (2020), around the ages of 8 to 10, there is significant development at all attentional levels, since the highest attentional levels are achieved at the age of 9, for this reason children present more receptivity and improvement in academic performance. Visual attention is a major component that involves the initial development of learning in the area of ​​writing and arithmetic. It could also be deduced that there is selective, visual, focused and planned attention.